Absorbance photometric technique to measure roll waves in a free surface of a non-Newtonian fluid flow - da Cunha, Evandro Fernandes [UNESP]; de Oliveira Ferreira, Fabiana; de Freitas Maciel, Geraldo [UNESP]; Kitano, Cláudio [UNESP] (Elsevier, 2024)
This work aims to measure forced steady roll waves evolving non-Newtonian fluid flow by using absorbance photometric technique. Instabilities on the free surface of the uniform flow were induced by controlled air pulses, generating roll waves under specific conditions of Froude number and disturbance frequency. A systematic procedure was presented to clarify a compromise between the aqueous concentrations of Carbopol (with adequate viscosity) and methylene blue dye (avoiding optical opacity), providing both sensitivity and resolution for absorbance measurements. Roll waves amplitudes were also measured using an ultrasonic sensor in order to compare the results with the absorbance photometric technique. Given a channel inclination, six scenarios defined by different flow rates were tested, which allowed us to observe the generation of roll waves as a succession of shocks. The measured profiles showed a better precision (maximum error of 0.11 mm against 1.37 mm, for pump rotation equal to 475 RPM) using the absorbance photometric technique compared to the ultrasonic system, respectively.
Keywords: Absorbance; Flow; Free surface; Non-Newtonian fluid; Photometric technique; Roll waves; Shock waves; Ultrasonic system